The Added Worker Effect - Lundberg, Shelly (Journal of Labor Economics, 1985)
The term "added worker effect" usually refers to a temporary increase in the labor supply of married women whose husbands have become unemployed. This paper presents a new approach to the empirical study of the added worker effect, which emphasizes the role of employment uncertainty and credit constraints in generating short-run participation and employment patterns. The estimates are based on employment transition probabilities rather than static measures of labor supply and are used in a dynamic simulation of changes in the employment and participation rates of wives following an exogenous increase in unemployment among their husbands. The results show a small but significant added worker effect, at least for white families, and suggest that the apparent disagreement among previous studies may stem from different approaches to measuring responses to a transitory event such as an unemployment spell.